IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PEMBANGUNAN SISTEM HUKUM PIDANA DI INDONESIA - Erfandi Erfandi (Universitas Negeri Malang, 2016)
It should be recognized the draft Penal Code or the Criminal Code applied in Indonesia was a legacy of Netherland colonialism and imperialism regime which had colonized this country for 350 years. Badly, the book which is used as criminal law guidelines is still applicable in Indonesia, although the life and traditions of society are far different from those in the Netherlands. Even though, there are a few additions and subtractions to the Criminal Code provisions, but the nature of imperialism and capitalism remains rooted in the Penal Code. Therefore, in order to revise the Penal Code voiced intensively by various elements of society lately, it is highly recommended inserting appropriate norms to the values of Pancasila as the implementation of national ideology which is complex and civilized into the criminal law system in Indonesia. http://dx.doi.org/10.17977/um019v1i12016p023